Умови формування пружних переміщень у технологічній системі при механічній обробці - Новіков, Федір Васильович; Іванов, І. Є. (НТУ "ХПІ", 2013)
The paper offers a theoretical approach to the calculation and analysis of the accuracy of processing parameters with the elastic displacements occurring in the technological system. On the basis of the theoretical results obtained implementing the conditions for the best possible performance for a given precision machining machined surface. Practical recommendations for the effective management of the cutting process.
Keywords: інструмент різальний; точність обробки; похибки обробки; режим різання